MOLECULAR IDENTIFICATION AND CHARACTERIZATION OF CITRUS TRISTEZA VIRUS COAT PROTEIN FROM THE PUNJAB PROVINCE OF PAKISTAN - R. Haq; S. Naz (Journal of Animal and Plant Sciences, 2018)
Citrus is an important commercial crop around the globe including Pakistan that is being attacked by various pathogens including Citrus tristeza virus (CTV). The present study was carried out to investigate the molecular identification and characterization of the most lethalCitrus tristeza virus (CTV) from the major citrus producing region of Punjab (Pakistan). The total RNA from different varieties of sweet oranges, mandarins, grapefruits, lemons, limes, kumquats and important rootstock was extracted to be used as template for PCR using primers for the universal coat protein detection of CTV. Total RNA was extracted from the sweet oranges, mandarins, grapefruits, lemons and limes, kumquats and important rootstock varieties, which were then converted to cDNA to be used as a template in a conventional PCR using primers for the universal coat protein detection of CTV.A total of 250 samples were screened out of which 25 (10%) samples were found positive. The number of positive samples from each group includes20/100 sweet oranges, 2/70 mandarins, 1/32 lemon and limes and grapefruit 2/30 were observed. The results from the analysis of the PCR assay confirmed the presence of CTV as the gene fragment was amplified from by PCR at desired size of 672bp.The desired PCR amplified product was ubjected to Sanger sequencing and phylogenetic relationship using MEGA 7.0. showed 99% homology with the aligned American isolates.The amplified product was then sequenced and analyzed phylogenetically using MEGA 7.0 that showed 99% homology with American isolates.Hence the study proved to produce a significant preliminary data showing the current status of CTV that can be used for the creation of a pathogen tested citrus germplasm program for citrus growers in Pakistan. This study was conducted to evaluate the current CTV status of the citrus germplasm collection of a citrus research institute in Punjab, Pakistan, in order to produce preliminary data that can be used for the creation of a pathogen-tested citrus germplasm program for the citrus growers in Pakistan. Variegation) ( CTV, CVV) and many others all over the
Keywords: Citrus tristeza virus; Coat protein; Molecular characterization; Phylogenetic analysis.